Upaya Pemerintah Daerah Dalam Penanggulangan Pernikahan Usia Dini Di Desa Majannang Kecamatan Maros Baru Kabupaten Maros - Hidayanti, Nur; Razak, Andi Rosdianti; Parawangi, Anwar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study was to determine the efforts of localn governments in tackling early marriage in Maros Regency. This study used qualitative research. The informants in this study wete 12 people, data collection techniques used interview, observation and documentation. Data analysis were data reduction, data presentation and conclusion. The results of this study showed that the government efforts in overcoming early marriage in Maros Regency had very good performance, but early marriage still did not achieve satisfactory results, seen from four dimensions, namely: input was a policy issued by the local government in handling early marriage. The second was outputs (activities)that could be in the form of physical funds or non-physical in the prevention of early marriage. The third was the outcome(results) of the local government had launched an excellent program but the results achieved were not very satisfying. The last was the benefits about the adverse effects of early marriage and the impact of both the positive and negative effects of early marriage.